A Love That Reforms: Improving Gender Relations by Contesting Typologies of Women in La Comédie de Mont-de-Marsan and L’Heptaméron 10 and 42 - Brock, Theresa (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2020)
This article examines how two texts by Marguerite de Navarre contest the tendency in courtly and ecclesiastical literature to reduce women to typologies based on sexuality, spirituality, and notions of virtue. In place of simplified typologies, Marguerite’s writings can be read as depicting women’s multidimensional personhood as they strive to live out a sincere Christian faith in a society that fixates on their sexuality. Ultimately, this study argues that when read together, La Comédie de Mont-de-Marsan and L’Heptaméron 10 and 42 suggest the need for women to develop a practical brand of Christian wisdom that will help them to reform both gender relations and patriarchal institutions, thereby replacing misogynistic discourses and behavioural patterns with respect for women’s humanity.